معالم الشّخصية الاجتماعية للرّسول (Al Basirah, 2020)
The personality of the messenger, before and after prophethood wasadmired by both; friends and foes. whoever learned or read about him withoutprejudice is bound to lose skepticisim, and not hesitate to appreciate hisgreatness, acknowledge his favours, and follow his path, for the bright lightsof his persona(s.a.w) dissipates the darkness of shirk and Ignorance,softens thestiffness of hearts, makes orphans forget the bitterness of their plight, thebereavedـــ the pain of bereavement,the needyـــ the stings of want, and theweak ـــthe weight of indignity. Despite being met with great harm from thoseclosest to himself; his relatives, he chose patience and kindness. He knew noinjustice nor cajolery. He was kind and courteous to his neighbors, a step shyof bequeathing them. He commanded children be kind to their parents even ifthey were Mushrik. He emphasized on mothers, for they are delicate, andmore deserving of care and kindness. Women were honored and enjoyed adistinguished place, as the Prophet had returned to them their forsakenhumanity during the preceeding dark era in which they held no significance.His favors weren’t exclusive to his wives but extended to include all women,Muslim or otherwise, he treated them with kindness and calledthem“AlQawareer”(Glass flasks) for they are pure and delicacte. He correctedthem when they erred, and equated men who toil to meet their needs withthose who fend off enemies on fronts. He commanded in his last momentsthat women be treated righteously. The French orientalist, Lewis Seidio, wasimpressed by the personality of the prophet(s.a.w)and the manner in which heconducted himself and treated other people, which induced them to call him“the truthful, the honest”, until he was entrusted with the message and begancalling his people to the one true god, to which they opposed him viciously,but heeded his call eventually. He was kind to the elderly,tender to the young,a teacher and a wise man in service of his society, a stream of knowledge andmanners to the whole world. this paper discuses in detail those traits.
Keywords: prophet,landmarks,social,aspect,women,orientalist,seidio, AlQawareer,bequeathing.